Física para geografia: desafios de uma proposta pedagógica interdisciplinar - Alves, Aureliano de Oliveira (2008)
This study has as its aim the elaboration, presentation and application of a proposal which makes possible an inter-disciplinary relationship between knowledge of physics and geography in the graduation course for forming geography teachers in the Dom Aureliano Matos Faculty of Philosophy in the city of Limoeiro do Norte in the State of Ceára. Initially, we observe in pertinent literature and opinions of specialists what capacities and abilities are suggested for a future teacher of geography. Following that, we select subject matter which broaches upon physic concepts and may be contextualized within topics present in the daily fare of a geography teacher, such as natural phenomena related principally to natural environment and climate, envolving astronomic features, using didactic materials and resources in easily understood language and without the excessive presence of mathematical formulas. An evaluation of the experience allows us to affirm that inter-disciplinary treatment, as an important alternative for curriculam organization, when applied in the classroom shows that there is better learning, a reduction in class evasion and a significant fall in failures when compared with traditional proposals for the teaching of physics in relation to geography. On the other hand, it is notable that to maintain and augment such measures it is a challenge to be met, with the purpose that students of other courses may perceive that physic concepts have much to do with their reality, and that understanding them is relevant for their professional and personal formation